The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s42108-020-00101-5
|View full text |Cite|
|
Sign up to set email alerts
|

An analysis of energy diversification and transition trends in Africa

Abstract: Unlike energy security, energy diversification, which is an essential precursor for energy security and sustainability transitions, has not received much scholarly attention, especially in Africa. Applying the Energy Mix Concentration Index method (a modified version of the Herfindahl-Hirschman Index), this study examined energy diversification and transition trends in Africa's top ten economies over an 18-year period, from 2000 to 2017. Data were obtained in July 2020 from the African Union Energy Commission'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 37 publications
1
17
1
Order By: Relevance
“…We used bioenergy in our study because the Ghanaian authorities have identified it as the main renewable, dispatchable and spatially distributed technology available in the country, and it can use the residues from various stages of agricultural and forestry activities, mainly from crop harvesting, wood logging, and from municipal wastes and other commercial and domestic activities 37 . Our results are consistent with previous studies highlighting the importance of a diversified expansion of renewable technologies to reduce energy system vulnerabilities 49 . The proposed framework enables pragmatic and detailed spatial designs of how the river basin and energy networks should best be connected, expanded, and their operations synergized.…”
Section: Articlesupporting
confidence: 93%
“…We used bioenergy in our study because the Ghanaian authorities have identified it as the main renewable, dispatchable and spatially distributed technology available in the country, and it can use the residues from various stages of agricultural and forestry activities, mainly from crop harvesting, wood logging, and from municipal wastes and other commercial and domestic activities 37 . Our results are consistent with previous studies highlighting the importance of a diversified expansion of renewable technologies to reduce energy system vulnerabilities 49 . The proposed framework enables pragmatic and detailed spatial designs of how the river basin and energy networks should best be connected, expanded, and their operations synergized.…”
Section: Articlesupporting
confidence: 93%
“…Our analysis deviates from Rubio-Varas and Muñoz-Delgado (2019) and Akrofi (2021) and contributes to the current literature in various ways. First, we focus on 64 developing and developed countries in all regions rather than specific countries in one region, such as Africa or Europe.…”
Section: Introductioncontrasting
confidence: 58%
“…The variety of energy sources has increased since the 1990s. However, this issue does not automatically imply that all the countries follow similar energy diversification patterns or use similar energy sources (Akrofi, 2021). Therefore, we introduce a comparable index to measure energy mixes (portfolio) and analyze the diversification pattern in different countries over decades.…”
Section: The Index Of Energy Consumption Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to International Energy Agency (IEA) urbanisation and population growth with a lack of proportional investment in the energy sector is also another factor undermining energy security in SSA (IEA, 2019). Although renewable energy diversification is an essential precursor for energy security and sustainability (Akrofi, 2021), a lack of efficient and economically sustainable power systems, coupled with costly infrastructure investments currently constrain the penetration of those resources in the electricity mix in SSA (Pistelli, 2020). Energy insecurity pushes many households in SSA to rely on unsafe sources of energy including open fires for cooking, and lighting, with severe health implications such as acute respiratory infections and lung cancer (Boateng et al, 2020).…”
Section: Few Insecurity Factorsmentioning
confidence: 99%